Occupational Priorities in Children with Cerebral Palsy Based on Gross Motor Function and Manual Ability Levels: A Comparison Between Children’s and Caregivers’ Perspectives: Occupational Performance in CP - Boroumand, Samira; Hassani Mehraban, Afsoon; Amini, Malek; Salimi, Yahya; Azad, Akram (Iranian Journal of Child Neurology, 2026)
Objectives: The aim is to compare the occupational priorities of children with Cerebral Palsy (CP) who have mild to moderate motor impairments with those of their caregivers. Additionally, the goal is to explore the connections between these priorities—considering occupation, occupational performance, and satisfaction with performance—and the children’s levels of gross motor function and manual ability. Materials & Methods: This cross-sectional study included 58 children with CP aged 6-12 years (mean ± SD: 9.2 ± 2.2) and their 58 caregivers (mean ± SD: 38.5 ± 7). Assessments were conducted using the Canadian Occupational Performance Measure, the Manual Ability Classification System, and the Gross Motor Function Classification System. Data was analyzed using descriptive statistics, Pearson correlations, Fisher’s exact tests, and multiple linear regression. Results: The top three occupational priorities, in order, were personal care and functional mobility for both children and caregivers, with active recreation for children and school/study-related activities for caregivers Significant associations were found between children’s occupational priorities areas and manual ability (V = 0.43, p < 0.001) and gross motor function level’s (V = 0.32, p = 0.016), caregivers’ occupational priorities areas and manual ability level’s (V = 0.49, p < 0.001), and children’s satisfaction with both caregivers’ satisfaction (r = 0.416, p = 0.031) and performance (r = 0.413, p = 0.032 score. Conclusion: Although children with CP, presenting mild to moderate motor impairment, and caregivers shared two top occupational priorities, differences in other priority emphasize the need to consider children’s perspectives in interventions Children’s motor function influenced occupational priorities selection, and their satisfaction was more affected by caregivers’ perceptions than by their own performance, highlighting the need to raise caregivers’ awareness during therapy